2010
DOI: 10.1007/s10815-010-9475-7
|View full text |Cite
|
Sign up to set email alerts
|

Spindle and chromosome configurations of in vitro-matured oocytes from polycystic ovary syndrome and ovulatory infertile women: a pilot study

Abstract: Purpose To evaluate the meiotic spindle and chromosomal distribution of in vitro-matured oocytes from infertile nonobese women with PCOS and male or tubal causes of infertility (controls), and to compare in vitro maturation (IVM) rates between groups. Methods Seventy four patients (26 with PCOS and 48 controls) undergoing stimulated cycles of oocyte retrieval for ICSI were selected prospectively. Thirteen PCOS patients and 27 controls had immature oocytes retrieved submitted to IVM. After IVM, oocytes showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The full text of these studies was examined thoroughly, resulting in the exclusion of 91 (Table A in S2 File ). Eventually, 11 studies were considered eligible for inclusion in the meta-analysis [ 11 13 , 18 , 23 , 34 – 39 ]. Characteristics of the studies included are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The full text of these studies was examined thoroughly, resulting in the exclusion of 91 (Table A in S2 File ). Eventually, 11 studies were considered eligible for inclusion in the meta-analysis [ 11 13 , 18 , 23 , 34 – 39 ]. Characteristics of the studies included are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The two largest studies published so far investigating the research question were by Child et al and Junk et al conducted in 2001 and 2012, respectively [ 12 , 36 ], involving 99 PCOS patients and 108 controls in total. The comparison group consisted of PCO women in five studies [ 11 13 , 34 , 36 ] and in eight of women/couples suffering from other causes of sub-fertility [ 12 , 13 , 18 , 23 , 34 , 37 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 B1-B3). Meiotic aberrations consisted of abnormal spindle configuration and/or abnormal chromosomal organizations (13).…”
Section: Immunofluorescence Staining and Scanning Confocal Microscopymentioning
confidence: 99%
“…However, all oocytes of the cited study were obtained from PCOS women, and the in vitro-matured oocytes analyzed in the study were obtained from unstimulated cycles. Another published report evaluated the meiotic spindle and chromosome distribution of in vitro-matured oocytes from infertile nonobese women with PCOS and subjects with male or tubal causes of infertility (controls) and found that in vitro-matured oocytes obtained from stimulated cycles of nonobese PCOS patients did not have an increased ratio of meiotic abnormalities [38]. The proportion of meiotic anomalies observed (35.3%) was similar to that found in the present study (42.9% spindle anomalies in the nonobese group).…”
Section: Discussionmentioning
confidence: 99%